1998
DOI: 10.1097/00005392-199812020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Features of Benign and Malignant Prostate Epithelial Cells

Abstract: We propose that topographic infidelity of proliferation produces a population of secretory cells replicating in the absence of key genome protective mechanisms, thus setting the stage for an accumulation of genomic alterations and instability in high grade prostatic intraepithelial neoplasia. This action occurs along with activation of telomerase, resulting in an immortal clone capable of developing into invasive carcinoma. The model predicts that genome protection remains intact in BPH, minimizing its maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 97 publications
7
95
0
3
Order By: Relevance
“…The epithelium in the prostate is composed of two cell layers, a basal and a secretory cell layer. The basal layer consists primarily of transiently amplifying cells, expressing highmolecular-weight cytokeratins (K14 and K5), and probably also houses the stem cell population that gives rise to the transiently amplifying cells (Bonkhoff et al 1994;Collins et al 2001;Xin et al 2003;De Marzo et al 1998b;Hall et al 2002). Transiently amplifying cells differentiate into intermediate cells, which are positive for K18, and this step of differentiation is associated with growth arrest and later with the expression of proteins that are necessary for the secretory functions of the prostate in response to androgen stimulation (De Marzo et al 1998;Fry et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The epithelium in the prostate is composed of two cell layers, a basal and a secretory cell layer. The basal layer consists primarily of transiently amplifying cells, expressing highmolecular-weight cytokeratins (K14 and K5), and probably also houses the stem cell population that gives rise to the transiently amplifying cells (Bonkhoff et al 1994;Collins et al 2001;Xin et al 2003;De Marzo et al 1998b;Hall et al 2002). Transiently amplifying cells differentiate into intermediate cells, which are positive for K18, and this step of differentiation is associated with growth arrest and later with the expression of proteins that are necessary for the secretory functions of the prostate in response to androgen stimulation (De Marzo et al 1998;Fry et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Basal cells preferentially survived androgen ablation whereas 90% of luminal epithelial cells were lost through programmed cell death [25]. The surviving epithelial cells appeared androgen independent; however they remained responsive to exogenous androgen treatment [26]. Basal cells exhibited higher proliferation rates than luminal cells in normal and hyperplastic acini [27].…”
Section: Origin Of the Prostate Stem Cellmentioning
confidence: 99%
“…Approximately 70% of the cells expressing proliferation-associated antigens such as Ki-67 were phenotypically basal cells [27]. Neonatal rat prostatic buds co-expressed basal cell cytokeratins 5 and 14 as well as luminal cell cytokeratins 8 and 18 [26]. In archival human tissues representing primary prostate carcinoma and high grade prostatic epithelial neoplasia (PIN), De Marzo et al identified an intermediate layer of p27 Kip1 -negative cells sandwiched between p27 Kip1 -positive basal and luminal cells and hypothesized that these cells were competent for entry into the cell cycle [22].…”
Section: Origin Of the Prostate Stem Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in only 5.2% of the 135 cases tumor eradication remains debatable. Although this seems to be possible in theory [22], missed or overlooked tumor remnants can never be definitely excluded because: (1) Endocrine pretreatment is known to reduce the tumor volume [6]and causes a variety of additional regressive changes of varying severity sometimes leaving only scattered isolated tumor cells behind [23, 24, 25, 26, 27, 28, 29, 30]. This makes histological tumor detection very difficult.…”
Section: Discussionmentioning
confidence: 99%